Дослідження методів побудови транзикційної пам'яті з апаратної підтримкою і без неї - Стрименешенко, О. С.; Шалімов, О. А. (ХНУРЕ, 2020)
This topic is very relevant, since lately more there is a transition from sequential to parallel computing, and existing development tools for parallel programs are complex and not effective enough. With development of multicore processors has created a need for alternative solutions that provide a simple and understandable way to provide access to shared memory.